X-Ray Fluorescence Analysis of XII–XIV Century Italian Gold Coins. (8th October 2014) - Baldassarri, Monica; Cavalcanti, Gildo de Holanda; Ferretti, Marco; Gorghinian, Astrik; Grifoni, Emanuela; Legnaioli, Stefano; Lorenzetti, Giulia; Pagnotta, Stefano; Marras, Luciano; Violano, Eleonora; Lezzerini, Marco; Palleschi, Vincenzo
Abstract : An extensive analytical study has been performed on a large number of gold coins (Norman-Swabian Augustale and Tarì, Grosso of Lucca, Florin of Florence) minted in Italy from the end of XII century to XIV century. The X-ray fluorescence (XRF) technique was used for verifying the composition of the coins. XRF is a nondestructive technique particularly suited for in situ quantitative analysis of gold and minor elements in the precious alloy. The Florins turned out to have a gold content very close to 24 carats (pure gold) although in a couple of cases we observed relatively high concentrations of iron (around 2%) or lead (around 1%). The Grosso of Lucca has a similar composition, with a measured gold content around 97% due to a higher silver percentage (about 2%), with respect to the average Florin. The Augustali analyzed showed, on average, a gold content around 89%. The average gold content of the Tarì analysed is around 72%, with a relatively large variability. The analysis revealed the use of native gold for the coinage of the Florins, excluding the possibility of recycling gold coming from other sources. On the other hand, the variability observed in the compositions of the Tarì and Augustali could suggest the reuse of Islamic and North African gold. The study could shed some light on the sudden diffusion of gold coins in Italy around the first half of XIII century, allowing hypotheses on the provenience of the gold used for a coinage that dominated the economic trades from then on.